Criminology and Sociology in the Revista de Ciencias Jurídicas - Salas Porras, Ricardo (2023)
This essay takes a look at the various works that have been published throughout the sixty years of existence of the Revista de Ciencias Jurídicas, in the field of scientific evolution and teaching of the binomial Criminology and Sociology. From this collection, the contributions estimated to be most relevant have been selected, trying to group them according to common features that allow their analysis by subset